Pengembangan Agrowisata Berbasis Ketahanan Pangan Melalui Strategi Komunikasi Pemasaran di Desa Serang Purbalingga - Sulaiman, Adhi Iman; Kuncoro, Bambang; Sulistyoningsih, Endang Dwi; Nuraeni, Hikmah; Djawahir, Fatmah Siti (Jurnal The Messenger, 2017)
The study aims to analyze the developing agrotourism based on food security through marketing communications strategy. The research method used Participatory Rural Apprasial, data was collected through interviews, observation, documentation and focus group discussion with interactive analysis and SWOT analysis. The informant research   through purposive sampling of 30 people as a community worker in the Serang village, Karangreja subdistrict of   Purbalingga Regency. The results showed corporation effort possession village have not been able to manage the organization, marketing, promotion, developing business units and partnerships, thus require integrated marketing communications model on the empowerment of agrotourism based on food security in the Serang village.